1987
DOI: 10.1002/j.1460-2075.1987.tb02389.x
|View full text |Cite
|
Sign up to set email alerts
|

The cell envelope of Thermoproteus tenax : three-dimensional structure of the surface layer and its role in shape maintenance

Abstract: The sulphur-dependent archaebacterium Thermoproteus tenax has a cylindrical cell shape variable in length, but constant in diameter. Its whole surface is covered by a regular protein layer (S-layer). The lattice has p6 symmetry and a lattice constant of 32.8 nm. The three-dimensional reconstruction from a tilt series of isolated and negatively stained S-layer shows a complex mass distribution of the protein: a prominent, pillar-shaped protrusion is located at the 6-fold crystallographic axis with radiating arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…For cloning experiments, plasmids pUC19, pNEB193 and pQE30 were routinely used (Yanisch-Perron et al, 1985 ;New England Laboratories ;Qiagen). For mating experiments, DNA fragments were inserted into pAT113 (Trieu-Cuot et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cloning experiments, plasmids pUC19, pNEB193 and pQE30 were routinely used (Yanisch-Perron et al, 1985 ;New England Laboratories ;Qiagen). For mating experiments, DNA fragments were inserted into pAT113 (Trieu-Cuot et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Few data are available concerning the function of S-layers. Nevertheless, some studies have shown that the S-layer is involved in cell integrity and shape maintenance in S. MESNAGE, M. HAUSTANT and A. FOUET archaea, in which it is often the only cell-envelope component (Mescher & Strominger, 1976 ;Wildhaber & Baumeister, 1987). In some pathogenic bacteria, the S-layer is involved in resistance to complement-mediated killing or interaction with host cells and molecules (Pei & Blaser, 1990 ;Kotiranta et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…They probably act as protective coats, molecular sieves or ion traps (for a review, see Beveridge and Graham, 1991;Messner and Sleytr, 1992). In Archaebacteria, they determine and maintain cell shape (Mescher and Strominger, 1976;Wildhaber and Baumeister, 1987). In some cases, S-layers were also identified as virulence factors (Evenberg and Lugtenberg, 1982;Fujimoto et al, 1991;Wang et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Archaeal cell envelopes often consist solely of a paracrystalline protein monolayer (S layer) (reviewed by Messner & Sleytr, 1992) which is in peripheral contact with the outer face of the plasma On: Fri, 11 May 2018 19:18:02 M. FIRTEL, G. B. PATEL a n d T. J. BEVERIDGE membrane (PM) (Konig, 1988). Archaeal S layers contact the PM via inner surface extensions which probably embed in the hydrophobic region of the PM (Hovmoller et al, 1988;Baumeister et al, 1989;Wildhaber & Baumeister, 1987;Phipps e t al., 1990;Firtel et al, 1993). The S layer is formed from a single type of interlocking polypeptide bound together by noncovalent forces, and is structured to produce transversing channels that are apparent in negative stain transmission electron microscopy (TEM) (Hovmoller et al ,1988) and in ultrafiltration assays (Sira & Sleytr, 1987a).…”
Section: Introductionmentioning
confidence: 99%